Field Strength of Network-Modifying Cation Dictates the Structure of (Na-Mg) Aluminosilicate Glasses - Sreenivasan, Harisankar; Kinnunen, Paivo; Adesanya, Elijah; Patanen, Minna; Kantola, Anu M.; Telkki, Ville-Veikko; Huttula, Marko; Cao, Wei; Provis, John L.; Illikainen, Mirja (Frontiers in Materials, 2020)
Aluminosilicate glasses are materials with a wide range of technological applications. The field strength of network-modifying cations strongly influences the structure of aluminosilicate glasses and their suitability for various applications. In this work, we study the influence of the field strength of network-modifying cations on the structure of [(Na2O)1–x(MgO)x(Al2O3)0.25(SiO2)1.25] glasses. Due to the higher cation field strength of magnesium than sodium, magnesium prefers the role of network modifier, while sodium preferentially acts as a charge compensator. When magnesium replaces sodium as network modifier, Q3 silicon species are converted into Q2 species. The replacement of sodium with magnesium as charge compensator leads to the following changes: (1) the proportion of aluminum-rich Q4 species [Q4(4Al) and Q4(3Al)] decreases, while the proportion of aluminum-deficient Q4 species [Q4(2Al) and Q4(1Al)] increases; and (2) there is an increased tendency for phase separation between silica-rich and alumina-rich glasses.